Multifocal papillary carcinoma of the thyroid with heterotopic ossification and extramedullary hematopoiesis associated with a lipomatous follicular nodule - Xavier, José Cândido Caldeira; Camilo, Deolino João; Conrado-Neto, Sebastião [UNESP]; De Castro Lippe, Ana Cláudia Severo; Mattar, Neivio José (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Heterotopic ossification has been described in papillary thyroid carcinoma in association with high incidence of extrathyroidal invasion, multifocality, lymph node metastasis, and older age. Nevertheless, it has not been described as a specific subtype of papillary thyroid carcinoma, because of its rarity. We described the case of an 80-year-old female patient, with familial history of papillary thyroid carcinoma. In the annual screening examination, she was diagnosed with thyroid nodules. The patient was submitted to a thyroidectomy because the fine needle aspiration cytology was positive for malignancy according to the Bethesda classification. The surgical specimen analyses showed a multifocal papillary carcinoma with one major lesion in the left lobe measuring 0.9 cm, and two small lesions (0.4 cm and 0.2 cm) in the right lobe. Only the biggest lesion in the right lobe had the osteoid matrix with rare osteoclasts and fat metaplasia with progenitor cells. There was perineural invasion, but vascular invasion was not identified. The margins were free and there was no extrathyroidal extension. In the left lobe there was an oncocytic nodule and a lipomatous follicular nodule. In recent years there has been a significant increase in the diagnosis of thyroid cancer, mainly because of the finding of microcarcinomas as a result of many requests for cervical image exams. Future studies may define (i) whether papillary thyroid carcinoma with heterotopic ossification is a true histological variant; (ii) the causes of that alteration; and (iii) eventual follow-up implications.
Keywords: Carcinoma; Heterotopic; Ossification; Papillary; Thyroid Gland; Thyroid Neoplasms